The Muslim Continuum: An Analytical Model of Religiosity and Socio-Political Diversity in Muslim Minority Environments. Issue 2 (2nd April 2016) - Randeree, Kasim
Abstract: This paper examines the challenges facing Muslim societies in the early part of the twenty-first century. The paper examines tensions between "liberal" interpretations of Islam and extreme views within a globalisation paradigm and how these are changing. Specifically, the work investigates how the spotlight on Islam and its adherents in a post-9/11 world has manifest among Muslim individuals, groups and societies and how these may change to accommodate or react to the shifting global frame of mind towards Islam and the Muslims. Analysis is provided within the context of Muslim minority dwellers, with focus on Muslims living in Britain. The paper further proposes a fundamentalism continuum based on Dekmejian's 1 model and analyses its impact on the Muslim Diaspora.